As políticas de inclusão escolar da rede pública estadual de educação básica, na cidade de Uberlândia-MG (2020/2022) - o Plano de Desenvolvimento Individual (PDI) como instrumento da escola - Ponciano, Luhany Ercleide (2022)
This research is the result of an investigation at Master's degree of the Post-Graduation Program in Education at the Federal University of Uberlândia, inserted in the research line “State, Policy and Management in Education”. The object of our study is the relationship between the Individual Development Plan (PDI) and inclusion at school. The following questions are part of the problem studied: Are there relationships between inclusive education policies and the student's Individual Development Plan (PDI) at schools? What do the legislation and Pedagogical Political Projects of schools say about this? Is there coherence between these instruments and their proposals? What do the legislation and Pedagogical Political Projects of two state schools in Uberlândia say about this in 2020 and 2021? The general objective was to understand what the relationship between inclusive education policies and the student's Individual Development Plan (PDI) is, as well as what the legislation and Pedagogical Political Projects of two state schools in the city of Uberlândia say about it (2020/2021). As the methodological paths of this investigation, a qualitative approach, within a critical perspective, was used, by means of a bibliographic research and document analysis. Two State Basic Education schools were part of the sample for data collection as they were willing to collaborate with the investigation, making their PPPs and PDIs available for analysis. As theoretical basis, the following authors were primarily used: Borges-Dalbério (2008); Freire (1967, 1982, 1983, 1987, 1992, 1996, 1999, 2003); Rivers (2010); Mantoan (2002, 2003, 2010); and Silva (2009), whose works are of great scientific wealth and their studies and contributions to the training of teachers in our country is worth mentioning. As a document analysis, the legislation referring to inclusive education policies on the PDI and the Political Pedagogical Projects (PPP) of the two state schools were investigated. The results showed that the PDI is important to mitigate the exclusion of students with disabilities at schools. This way, it is an essential tool and contributes to education inclusion. However, the PDI needs to be better understood, and explored, as there is still a lack of resources and initiatives for its inclusion in the daily life of the Basic Education School